Elaboration of a didactic sequence in the teaching of Chemistry structured in an active methodology with a generator theme: the coffee (Research, Society and Development, 2020)
The use of Active Methodologies in teaching is characterized by inserting the student as the center of the learning process, giving autonomy so that he can solve problems based on discussions, interactions and activities that require him to become an active agent in this process, seeking strategies, like digital technologies, for problem solving. In this context, the objective of this work was to elaborate, through an active methodology, a didactic sequence composed of activities planned to teach some contents in the teaching of basic chemistry through a generator theme, coffee. The didactic proposals were structured in: * Begin the History of Coffee in teaching with the enactment of Law 10,639 of 2003; * Insert themes for the context of Chemistry Teaching with other subjects, such as Geography, Biology, History and Mathematics; * Awakening in students the interest of the generator theme as a product for researching articles; * Study on the chemical composition of coffee and * Sensory analysis of different types of coffee. In this analogy, in order to contribute concepts to teaching, it is understood that the historical and technological references allow to identify great possibilities of contextualization that can be constructed through active concepts and methodologies applied in the chosen generator theme. In other words, this text seeks to develop a stimulus around the concepts and propositions about didactic sequence, which consists of methodological proposals for the organization and planning of teaching, with different aspects and emphases.